Clinical concerns on sex steroids variability in cisgender and transgender women athletes - Di Luigi, L.; Greco, E. A.; Fossati, C.; Aversa, A.; Sgrò, P.; Antinozzi, C. (International Journal of Sports Medicine, 2023)
In the female athletic community, there are several endogenous and exogenous variables that influence the status of the hypothalamus-pituitary-ovarian axis and serum sex steroid hormones concentrations (e. g., 17ß-estradiol, progesterone, androgens) and their effects. Moreover, female athletes with different sex chromosome abnormalities exist (e. g., 46XX, 46XY, and mosaicism). Due to the high variability of sex steroid hormones serum concentrations and responsiveness, female athletes may have different intra- and inter-individual biological and functional characteristics, health conditions, and sports-related health risks that can influence sports performance and eligibility. Consequently, biological, functional, and/or sex steroid differences may exist in the same and in between 46XX female athletes (e. g., ovarian rhythms, treated or untreated hypogonadism and hyperandrogenism), between 46XX and 46XY female athletes (e. g., treated or untreated hyperandrogenism/disorders of sexual differentiation), and between transgender women and eugonadal cisgender athletes. From a healthcare perspective, dedicated physicians need awareness, knowledge, and an understanding of sex steroid hormones` variability and related health concerns in female athletes to support physiologically healthy, safe, fair, and inclusive sports participation. In this narrative overview, we focus on the main clinical relationships between hypothalamus-pituitary-ovarian axis function, endogenous sex steroids and health status, health risks, and sports performance in the heterogeneous female athletic community.